Examination of the Factor Structure and Convergent Validity of the Child and Youth Resilience Measure – Revised (CYRM-R) in a Sample of Adolescents from Serbia - Žujović, Anja (Psihološka istraživanja, 2025)
The aim of this study is to examine the factor structure and convergent validity of the Serbian translation of the Child and Youth Resilience Measure ‒ Revised (CYRM-R). The analysis was conducted on a sample of 421 adolescents (age range: 15‒19; M = 16.86; SD = 0.89; 48% female). Confirmatory factor analysis (CFA) and exploratory structural equation modelling (ESEM) were conducted to assess the factor structure. After comparing several models, including the one-factor and two-factor CFA and ESEM models, the two-factor CFA model was adopted as the most suitable. The structure of the selected model corresponds to the originally proposed one and includes all items within the intra/interpersonal and caregiver factor. The findings show acceptable fit indices, good subscale reliability, and adequate convergent validity, as demonstrated by the associations with the measures of subjective well-being and internal resilience. The initial findings suggest that the translated scale could provide an adequate assessment of resilience resources among adolescents in Serbia, with the main limitation of the study being the lack of a risk context.
Keywords: Child and Youth Resilience Measure (CYRM-R); Serbia; validation